Pengaruh Pertumbuhan Ekonomi, Pengeluaran Konsumsi Rumah Tangga, dan Pengeluaran Pemerintah terhadap Indeks Pembangunan Manusia di Kota Surabaya - Firly Annisa; Wiwin Priana Primandhana (Syntax Corporation, 2023)
Economic growth is one measure that can determine whether a country's development efforts have been successful. Development is a cycle used to achieve national goals. Population growth, fundamental changes in the economic system, and income equality all contribute to a country's economic growth. To assess these aspects, human development indicators can be used. This research examines the influence of household consumption, government spending and economic growth on human development indicators in Surabaya city from 2011 to 2020. The Ordinary Least Squares approach is useful as conducting multiple linear regression analysis in this research. The results of the research show that public spending and economic expansion have a significant impact on HDI. However, HDI growth is only marginally affected by household consumption expenditure. The research recommends encouraging community empowerment, especially for the disadvantaged in education and health. This should be done in conjunction with increased strengthening of the economic structure and improvement of Surabaya's urban environment.